Review on the application of distributed optical fibre sensing in slope monitoring. Issue 1 (May 2020) - Ahmad, Izwan Shah; Kassim, Azman; Mohamad, Hisham
Abstract: The catastrophic event of slope failure which leads to the destruction of surrounding facilities and the loss of public lives has been acknowledge to be one of the most discussed topics in geotechnical engineering. Many conventional and modern techniques have been developed by researchers throughout the years to come out with a technique that is effective in monitoring slope deformation and thus, control the damage that may be caused by slope failure. Recently, the application of optical fibre sensing (OFS) has gained wide attention among researchers in slope monitoring application. It is known that OFS carries many advantages in terms of high resistivity towards electromagnetic interference, wide sensing range, and easy installation. This paper presents the overview of the recent development and application of OFS application in slope monitoring. Two main types of OFS namely Fiber Bragg Grating (FBG) and Distributed Optical Fibre Sensing (DOFS) which consists of Brillouin Optical Time Domain Reflectometry (BOTDR) and Brillouin Optical Time Domain Analaysis (BOTDA) are discussed in detail.